2009
DOI: 10.1590/s1678-77572009000300014
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between temporomandibular dysfunction and head and cervical posture

Abstract: Objective:This study aimed to evaluate the possibility of any correlation between disc displacement and parameters used for evaluation of skull positioning in relation to the cervical spine: craniocervical angle, suboccipital space between C0-C1, cervical curvature and position of the hyoid bone in individuals with and without symptoms of temporomandibular dysfunction.Material and Methods:The patients were evaluated following the guidelines set forth by RDC/TMD. Evaluation was performed by magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 10 publications
4
63
0
15
Order By: Relevance
“…This result reinforces the data of recent studies (19,20) , which did not find postural Note: G1 = temporomandibular disorder group; G2 = group without temporomandibular disorder Mann-Whitney test (p<0.05) Note: G1 = temporomandibular disorder group; G2 = group without temporomandibular disorder; SD = standard deviation; CPL/Hor = forward head posture angle; EVT/CVT = cervical lordosis angle; CVA = craniovertebral angle, referent to flexion/extension position of the head differences between patients with TMD and asymptomatic individuals. Such studies also used the cephalometric analysis and RDC/TMD to the TMD diagnostic.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result reinforces the data of recent studies (19,20) , which did not find postural Note: G1 = temporomandibular disorder group; G2 = group without temporomandibular disorder Mann-Whitney test (p<0.05) Note: G1 = temporomandibular disorder group; G2 = group without temporomandibular disorder; SD = standard deviation; CPL/Hor = forward head posture angle; EVT/CVT = cervical lordosis angle; CVA = craniovertebral angle, referent to flexion/extension position of the head differences between patients with TMD and asymptomatic individuals. Such studies also used the cephalometric analysis and RDC/TMD to the TMD diagnostic.…”
Section: Discussionsupporting
confidence: 93%
“…Flexion/extension head position in relation to superior cervical spine was measured through Rocabado craniovertebral angle, recently referred on literature (19)(20)(21) . This angle is formed by McGregor Plan (plan which tangencies the base of the occipital bone till it reaches the posterior nasal spine) and the Odontoid Plan (which comes from the top of the odontoid process of C2 till a most anterior and inferior point of the body of C2).…”
Section: Craniocervical Posture Evaluationmentioning
confidence: 99%
“…Most studies have centered mainly on the relationship of the position of the head and the cervical spine by means of angular measures in patients with TMD (6,9,(22)(23)(24) , and did not objectively quantify parameters related to mechanisms of postural balance, such as COP measures and velocity, which are regarded today as the two most accurate and reliable variables to quantify balance deficits (11,25) . These measures were addressed in the present study and support the reliability of the results observed by the authors for the population under study.…”
Section: Discussionmentioning
confidence: 99%
“…By palpating the cervical zygapophyseal joints examiners can differentiate between subjects with cervical pain and healthy subjects with 82 % sensitivity and a 79 % specificity [19][20][21][22][23][24][25] .…”
Section: -2 -2 -Examination Of Sectorsmentioning
confidence: 99%
“…However, a host of studies have failed to substantiate a supposed correlation between head posture and internal derangements of the temporo-mandibular joint nor have they found any significant differences in this regard between groups of patients with TMD and cranio-cervical disorders as compared to control groups 2,12,22,24,26 .…”
Section: -6 -Cranio-cervical Posturementioning
confidence: 99%